Manajemen Pengadaan Operasional Logsitik dan Distribusi Pemilu 2019 pada Komisi Pemilihan Umum Kota Balikpapan - Eva Yunita Lumban Gaol (Mahesa Research Center, 2022)
This article aims to find out and analyze management of Procurement of Logistics Operations and distribution of logistics for the 2019 election as well as analyzing obstacles in the procurement and distribution of Election Operations. The procedure for collecting information is by collecting and summarizing data that is not recorded in numbers but in the form of an explanation that is described and analyzed descriptively with a qualitative approach. Data obtained through interviews and library documents. The problem is focused on four main indicators in logistics distribution to support the completeness of the 2019 Election, namely, Logistics Management, Budget certainty, procrutment and logistics distribution. Therefore, logistics management and distribution have a very important role for the successful completion of the 2019 election, where the processes involved are interrelated with one another. The theory used in this problem is from Bowersox (2002) which states that the main logistics characteristics of logistics activities are the integration of various sizes and demands formovementand storage. The results of the research prove that due to a lack of communication between the Balikpapan City KPU and the RI KPU along with logistics providers, some of the logistics equipment is procured late, so that the arrival of logistics from providers does not coincide causing the logistics system to not work properly, obstacles in pawning and distribution of Election Operations namely the intervention of the commissioner in terms of procurement and raising prices in the appointed procurement directly resulted in state losses that had to be returned, and the lack of sending ballots caused delays in logistics and minimal transportation personnel, so that it became an obstacle in the distribution of logistics.